Paradox of Laws on Age of Consent for Children when Testing, or Participating in HIV/AIDS Research and Clinical Trials in South Africa - Paul T. Mtunuse; Tembela Mdunyelwa-Melane (E-Journal of Humanities, Arts and Social Sciences)
The purpose of the study was to explore the contradictions between the laws on the age of consent for children when consenting to test or participating in HIV/AIDS research and clinical trials exclusive of parental consent in South Africa. The methodology used was a qualitative method that incorporated a literature review, content analysis, internet sources, and databases to analyse children’s consent to testing and treatment. Consent for children when testing for or participating in HIV/AIDS research and clinical trials is a controversial issue. The paper submits a finding that while it is welcomed that children below 18 years may undergo testing or consent to research or clinical trials for HIV without parental consent, this is a paradox as it leads to legal contradictions. The inconsistencies are that whereas other laws allow children of 12 years of age to consent to testing or participation in HIV/AIDS research, other rules do not permit such a minor to act on his or her behalf if his or her health is harmed in the process, until 18 years. In conclusion, the researchers recommended that parental consent to HIV testing, research, or clinical trials of a minor child should not be excluded by law. The study’s contribution to scholarship is that it exposes inconsistencies in legislation that governs the age of consent for children and guides health professionals and researchers to understand the risks they assume when testing or conducting HIV/AIDS research or clinical trials.